Prolyl hydroxylase domain enzyme 2 is the major player in regulating hypoxic responses in rheumatoid arthritis. - Muz, B; Larsen, H; Madden, L; Kiriakidis, S; Paleolog, E (2012)
OBJECTIVE: Rheumatoid arthritis (RA) is characterized by hypoxia and the expression of hypoxia-inducible transcription factors (HIFs), which coordinate cellular responses to hypoxia. The objective of this study was to analyze the expression and regulation of prolyl hydroxylase domain (PHD) enzymes and factor-inhibiting HIF-1α (FIH-1), which regulate cellular HIF levels, and to study the roles of these enzymes in RA fibroblast-like synoviocytes (RA FLS). METHODS: The expression of PHD and FIH and downstream target genes was assessed by quantitative polymerase chain reaction and Western blotting. A small interfering RNA (siRNA) approach and an in vitro endothelial cell angiogenesis assay were used to analyze the roles of HIF hydroxylases. RESULTS: In human RA FLS, knockdown of PHD-2, but not knockdown of PHD-1 or FIH-1, dramatically augmented HIF-1α expression, modestly increased HIF-2α protein expression under normoxic conditions, and up-regulated HIF-dependent gene expression. In contrast, silencing of PHD-3 up-regulated HIF-2α but reduced HIF-1α, thereby decreasing the expression of HIF-regulated genes. A similar effect of PHD-2 knockdown was observed in osteoarthritis FLS (OA FLS) but not in nondiseased primary human dermal fibroblasts. These findings correlated with the induction of in vitro angiogenesis by supernatants from RA FLS and OA FLS transfected with siPHD-2 but not by supernatants from nondiseased fibroblasts or from siPHD-3-transfected cells. CONCLUSION: Our data suggest that PHD-2 is the major hydroxylase regulating HIF levels and the expression of angiogenic genes in arthritic cells. PHD-2 appears to regulate responses relevant to arthritis via HIF-α, highlighting the major importance of this enzyme in hypoxia- and angiogenesis-dependent inflammatory diseases such as RA.